2021
DOI: 10.1186/s12882-021-02375-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between baseline LDL-C and prognosis among patients with coronary artery disease and advanced kidney disease

Abstract: Background Lower low-density lipoprotein cholesterol (LDL-C) is significantly associated with improved prognosis in patients with coronary artery disease (CAD). However, LDL-C reduction does not decrease all-cause mortality among CAD patients when renal function impairs. The association between low baseline LDL-C (< 1.8 mmol/L) and mortality is unknown among patients with CAD and advanced kidney disease (AKD). The current study aimed to evaluate prognostic value of low baseline LDL-C level f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…This is also corroborated by the fact that not even statin medication correlates with the two OS markers in CKD-5d patients, which is in accordance with the observation of no beneficial effect by statins in any underlying CVD of these patients ( 79 81 ). This is corroborated also with our finding that LDL-C levels in CKD-5d patients correlate inversely with free cholesterol-OOH levels, and is also consistent with the finding that patients with advanced CKD and low LDL-C levels present higher risk for all cause death ( 16 ). All these findings further strengthen the disputed role of LDL-C as a reliable universal marker for CVDs development ( 12 , 13 , 15 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is also corroborated by the fact that not even statin medication correlates with the two OS markers in CKD-5d patients, which is in accordance with the observation of no beneficial effect by statins in any underlying CVD of these patients ( 79 81 ). This is corroborated also with our finding that LDL-C levels in CKD-5d patients correlate inversely with free cholesterol-OOH levels, and is also consistent with the finding that patients with advanced CKD and low LDL-C levels present higher risk for all cause death ( 16 ). All these findings further strengthen the disputed role of LDL-C as a reliable universal marker for CVDs development ( 12 , 13 , 15 ).…”
Section: Discussionsupporting
confidence: 92%
“…Despite the proven central causative role of oxLDL in atherosclerosis development (18), it has been only used in clinical studies as a prognostic marker for CVDs risk assessment but with contradictory results, possibly because it is being assessed non-specifically as a whole particle (16,(18)(19)(20)(21)(22)(23). This is mainly due to the lack of methods (a) for determination of specific oxidative modifications in the main protein/lipid components of oxLDL particles, and (b) for LDL fractionation into its main components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, comorbidities such as hypertriglyceridemia, low HDL cholesterolemia, and hyperuricemia were more frequently observed in individuals with the lowest LDL-C levels. Finally, the relationship between LDL-C and mortality from coronary artery disease has also been reported in a paradoxical hypothesis regarding the relationship with mortality, and patients with higher LDL-C at admission had not higher all-cause mortality compared to patients with normal or low LDL-C [ 32 , 33 ]. If high LDL-C were the cause, the effect should have been the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…Although coronary angiography is the gold standard for evaluating the severity of CHD, it has inevitable limitations as a high-cost, invasive procedure [ 3 ]. Studies have found that dyslipidemia is closely connected with CHD, and low-density lipoprotein cholesterol (LDL-C) is a crucial hazardous factor for CHD [ 4 ]. Meanwhile, serum cystatin C (CysC) can better predict the danger of cardiovascular events in high-risk patients than creatinine or glomerular filtration rate [ 5 ].…”
Section: Introductionmentioning
confidence: 99%